Studi Kualitatif Deskriptif tentang Proses, Hambatan, dan Strategi Guru dalam Pembelajaran BTA di Madrasah - Maharrissyah, Alihan Satra, Siti Adelia, M. Arif Pratama, Najamuddin, Hafnidah Ramadani (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
Learning to read and write the Quran (BTA) is an important aspect of Islamic education. However, in its implementation, various difficulties are still encountered by students, especially new students who do not yet have a basic understanding of reading and writing the Quran. This article aims to describe the process of implementing BTA learning, the types of difficulties experienced by students, the inhibiting factors, and teacher strategies for overcoming these difficulties in learning BTA in madrasas. This study used qualitative methods using interviews with BTA teachers. The results indicate that BTA learning is implemented through the stages of introduction, review of material, presentation of new material, question and answer sessions, and private and class recitation submissions. Learning difficulties experienced by students include poor Quranic reading skills, difficulty writing Arabic letters, and low interest in learning. The strategies implemented by teachers include grouping students based on ability, using engaging learning methods, providing motivation and rewards, and implementing the talaqqi and iqra methods in learning. These strategies are considered effective in improving students' Quranic reading and writing abilities.